International public financial management reform : progress, contradictions, and challenges - Guthrie, James, 1952-; Humphrey, Christopher; Jones, Lawrence R.; Olson, Olov (Research in public management (Unnumbered), 2005)
This book is intended to give readers detailed information and perspectives on the reform of financial management reform practices in a variety of national settings around the world. The chapters explore the reform agenda in each nation and factors that stimulated change. Each chapter addresses the extent of the influence of "New Public Management" concepts and practices on reform implementation. The nations whose experience is represented in this book are among the most often cited examples of progressive change to be examined and perhaps emulated by governments in other nations. In the introductory chapter the editors address the question whether and to what extent the financial management reforms detailed in the book reveal real progress or a progression of questions and dilemmas faced but not solved over the past several decades.